Lepore, The Whites Of Their Eyes - The Tea Party’s Revolution And The Battle Over American History - Hughes, Richard (Teaching History: A Journal of Methods, 2011)
Whether it is via bookstore shelves, television miniseries, or the political protests of the Tea Party movement, references to the Founding Fathers are seemingly everywhere in contemporary American culture. In The Whites of Their Eyes: The Tea Party’s Revolution and the Battle over American History, Jill Lepore, a historian of colonial America and frequent contributor to the New Yorker, examines how Americans on both the political right and the left have appropriated the memory of the American Revolution for political gain. As Lepore illustrates through numerous vignettes of well-known figures such as Benjamin Franklin, Thomas Jefferson, John Adams, and Thomas Paine, her emphasis is on our culture’s often deeply flawed collective memory rather than the discipline of history. For Lepore, much of the abuse of historical memory lies with the modern Tea Party movement, an organization she followed extensively in the Boston area in 2009 and 2010. The result is a political culture that increasingly argues, if not assumes, that our nation’s founding generation rebelled against the British in order to establish a Christian nation filled with white Europeans and wholly committed to cultural conservatism, low taxes, and an unregulated system of free enterprise. This culture, according to Lepore, is not just historically inaccurate; it is actually "anti-history" in that it suggests a seamless connection between the infallible heroes of the late eighteenth century and the complexity of our modern age.